2012
DOI: 10.1002/pen.23149
|View full text |Cite
|
Sign up to set email alerts
|

Fast and efficient manufacturing method of one‐ and two‐dimensional polyethylene terephthalate transmission diffraction gratings by direct laser interference patterning

Abstract: One‐ and two‐dimensional diffraction gratings were fabricated on commercial polyethylene terephthalate (PET) film by two beam direct laser interference patterning (DLIP) method using a pulse laser (10 ns) with a wavelength of 266 nm. The relative diffraction efficiency of the structured specimens (at 633 nm) in transmission mode was measured and correlated with the topological characteristics of the structured PET substrates. The obtained diffraction gratings made by DLIP show better or similar diffraction eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…technology. 47 For this work, a frequency quadrupled Q-switched laser head (Laser-export Co. Ltd., TECH-263 Advanced) with a maximum pulse energy of 50 µJ and operating at a wavelength of 263 nm and a pulse duration shorter than 3 ns was used. The laser beam has a Gaussian intensity distribution (TEM00) with a beam quality of M 2 < 1.3.…”
Section: 5fabrication Of the Grating Mastersmentioning
confidence: 99%
“…technology. 47 For this work, a frequency quadrupled Q-switched laser head (Laser-export Co. Ltd., TECH-263 Advanced) with a maximum pulse energy of 50 µJ and operating at a wavelength of 263 nm and a pulse duration shorter than 3 ns was used. The laser beam has a Gaussian intensity distribution (TEM00) with a beam quality of M 2 < 1.3.…”
Section: 5fabrication Of the Grating Mastersmentioning
confidence: 99%
“…The aforementioned, quality features make these substrates beneficial for large number of applications like, display devices, [ 9 ] diffraction grating, [ 10 ] organic and polymeric light emitting diodes [ 11–16 ] flexible solid‐state lighting, [ 17 ] organic and polymeric photovoltaics [ 18,19 ] flexible plasma displays [ 20 ] radio frequency system (RFID), [ 21 ] e‐paper, [ 22 ] medical applications, [ 11,23 ] sensors, [ 24 ] and smart textile. Polymeric substrates are drawing attention because of being flexible and transparent which is required for the applications where light has to exit (solid state lighting and displays applications) and enter (photo detection and photovoltaics).…”
Section: Introductionmentioning
confidence: 99%
“…[7] Flexible electronics can also be made using three dimensional printing technology for the future applications. [8] The aforementioned, quality features make these substrates beneficial for large number of applications like, display devices, [9] diffraction grating, [10] organic and polymeric light emitting diodes [11][12][13][14][15][16] flexible solid-state lighting, [17] organic and polymeric photovoltaics [18,19] flexible plasma displays [20] radio frequency system (RFID), [21] e-paper, [22] medical applications, [11,23] sensors, [24] and smart textile.…”
Section: Introductionmentioning
confidence: 99%
“…Laser interference patterning of bulk polymers has led to applications such as substrates for increasing the efficiency of solar cells and diffraction gratings . However, only a couple of studies on a certain polymer blend can be found laser interference patterning applied to polymer thin films, , and the ablation mechanism involved in the structuring process is still under discussion .…”
Section: Introductionmentioning
confidence: 99%
“…17 Laser interference patterning of bulk polymers has led to applications such as substrates for increasing the efficiency of solar cells 18 and diffraction gratings. 19 However, only a couple of studies on a certain polymer blend can be found laser interference patterning applied to polymer thin films, 20,21 and the ablation mechanism involved in the structuring process is still under discussion. 22 Moreover, the structures fabricated up to now using this lithographic technique are mainly micrometric, 23,24 and submicrostructuration has been scarcely reported in this field for polymers.…”
Section: ■ Introductionmentioning
confidence: 99%